Phylogenomic Insights into Diversity and Evolution of Nonpathogenic Xanthomonas Strains Associated with Citrus - Kanika Bansal; Sanjeet Kumar; Prabhu B. Patil (mSphere, 2020)
ABSTRACT Xanthomonas species are primarily known as a group of phytopathogens infecting diverse plants. Recent molecular studies reveal the existence of potential novel species and strains of Xanthomonas following a nonpathogenic lifestyle. In the present study, we report whole-genome sequences of four nonpathogenic strains from citrus (NPXc). Taxonogenomics revealed the surprising diversity, as each of these three isolates were found to be potential novel species that together form a citrus-associated nonpathogenic Xanthomonas species complex (NPXc complex). Interestingly, this NPXc complex is related to another nonpathogenic species, Xanthomonas sontii, from rice (NPXr). On the other hand, the fourth NPXc isolate was found to be related to nonpathogenic isolates from walnut (NPXw); altogether, they form a potential taxonomic outlier of pathogenic Xanthomonas arboricola species. Furthermore, genomic investigation of well-characterized pathogenicity clusters in NPXc isolates revealed lifestyle-specific gene content dynamics. Primarily, genes essential for virulence (i.e., type 1 secretion system [T1SS], T2SS and its effectors, T3SS and its effectors, T4SS, T6SS, adhesins, and rpf gene cluster) and adaptation (i.e., gum, iron uptake and utilization, xanthomonadin, and two-component systems) were depicted by comparative genomics of a Xanthomonas community comprising diverse lifestyles. Overall, the present analysis confers that nonpathogenic isolates of diverse hosts phylogenomically converge and are evolving in parallel with their pathogenic counterparts. Hence, there is a need to understand the world of nonpathogenic isolates from diverse and economically important hosts. Genomic knowledge and resources of nonpathogenic strains will be invaluable in both basic and applied research of the genus Xanthomonas. IMPORTANCE Xanthomonas citri is one of the top phytopathogenic bacteria and is the causal agent of citrus canker. Interestingly, Xanthomonas is also reported to be associated with healthy citrus plants. The advent of the genomic era enabled us to carry out a detailed evolutionary study of a Xanthomonas community associated with citrus and other plants. Our genome-based investigations have revealed hidden and extreme interstrain diversity of nonpathogenic Xanthomonas strains from citrus plants, warranting further large-scale studies. This indicates an unexplored world of Xanthomonas from healthy citrus plant species that may be coevolving as a species complex with the host, unlike the variant pathogenic species. The knowledge and genomic resources will be valuable in evolutionary studies exploring its hidden potential and management of pathogenic species.